Grapheme-color synaesthesia is associated with a distinct cognitive style - Meier, Beat; Rothen, Nicolas (Frontiers in Psychology, 2013)
In this study we investigated whether synaesthesia is associated with a particular cognitive style. Cognitive style refers to preferred modes of information processing, such as a verbal style or a visual style. We reasoned that related to the enriched world of experiences created by synaesthesia, its association with enhanced verbal and visual memory, higher imagery and creativity, synaesthetes might show enhanced preference for a verbal as well as for a visual cognitive style compared to non-synaesthetes. In Study 1 we tested a large convenience sample of 1046 participants, who classified themselves as grapheme-colour, sound-colour, lexical-gustatory, sequence-space or as non-synaesthetes. To assess cognitive style, we used the revised verbalizer-visualizer questionnaire, which involves three independent cognitive style dimensions (verbal style, visual-spatial style, and vivid imagery style). The most important result was that those who reported grapheme-colour synaesthesia showed higher ratings on the verbal and vivid imagery style dimensions, but not on the visual-spatial style dimension. In Study 2 we replicated this finding in a laboratory study involving 24 grapheme-colour synaesthetes with objectively confirmed synaesthesia and a closely matched control group. Our results indicate that grapheme-colour synaesthetes prefer both a verbal and a specific visual cognitive style. We suggest that this enhanced preference, probably together with the greater ease to switch between a verbal and a vivid visual imagery style, may be related to cognitive advantages associated with grapheme colour synaesthesia such as enhanced memory performance and creativity.